An exploratory psychometric network analysis of the college adaptation questionnaire in a sample of first year students - Thomas V. Pollet; Gabriele Adomaviciute; Nadine Haggag; Alyson Dodd; Sam G. B. Roberts (PLoS ONE, 2026)
The transition to university requires adjustment by students across many aspects of their lives. Multiple instruments have been developed to assess adjustment to life at university. One of the key instruments which has been widely adopted is the College Adaptation Questionnaire (CAQ). This measure is typically applied as a unidimensional measurement instrument. We examined the structure of the CAQ using a sample of 240 first year students at a UK university using psychometric network analyses. In addition, we examined whether the network structure for the items differed between first generation university students and non-first generation students. Using a Clique Percolation method, we found support for four clusters: satisfaction with university life and support (e.g., ‘I am very satisfied with the course of my studies’), social connection (e.g., ‘Sometimes I feel rather lonely’), adjustment to university (e.g., ‘I find it hard to get used to life here’) and student motivation (‘Sometimes I want to give it all up’). Network comparison tests suggested that the structure of the psychometric network did not significantly vary according to first generation status. We discuss our findings with reference to capturing student adjustment to university. Our findings suggest that the CAQ should preferably be used as a multidimensional instrument.